Pemilihan Lokasi Situs Di Palembang: Tinjauan Ekologi - Budi Wiyana (Berkala Arkeologi, 1996)
Culture is a human effort to adapt to its environment, including in terms of constructing a building or religious site. In constructing a building it is influenced by several factors, for example due to ecological, economic, political and religious factors. Site placement in the Palembang area can be approached from an ecological approach. Based on available data, the archaeological sites in Palembang are all located on the right side of the Musi River. It turns out that based on the altitude of the place, the right side of the river is higher than the left side.